Assessment in Science Learning Based on Ethnoscience - Hikmawati Hikmawati; I Wayan Suastra; A A Istri Agung Rai Sudiatmika (Jurnal Penelitian Pendidikan IPA, 2021)
This study aims to describe the assessment of ethnoscience-based science learning. The research data were collected through field observations and literature review. The research data were analysed descriptively. The results showed that: 1) there are five learning dimensions associated with ethnoscience-based assessment in science learning; 2) there are six dimensions of science related to ethnoscience-based assessment in science learning; 3) the type of assessment in ethnoscience-based science learning, divided based on the types of tests and non-tests; 4) construction of ethnoscience-based learning outcomes tests can be made from understanding to higher order thinking (HOT); 5) The ethnoscience-based essay test includes story questions about Sasak Sade Village, Bau Nyale Tradition, Sesek Weaving, Gendang Beleq, and Poteng Reket